Fiction Of The Novel “Lives Passed In A Dream” - Scientific advisor Kalandarova Dilafruz Abdujamilovna; Akhrorova Zarina Azamatovna (Genius Publishing Group, 2025)
This article is about Utkir Khashimov’s famous novel “Lives passed in a dream” describing the events of the Afghan war. Through the inner experiences of the heroes of the work, the author reveals the pains hidden in the heart of a modern person. Each line of the work is filled with complex paradoxes of life. The author describes the subtle and noble principles of human life, the connection between dreams and reality so skillfully that every reader feels like one of the heroes. This work expresses life and death, love and dreams, hope and hatred in a deep and profound way. The stylistic wealth, poetic spirit and imagery in the content of the author’s language lead the reader to his spiritual and spiritual world. Utkir Khashimov reveals the truths of life in an amazing way and invites a person to think deeply. Each event, each image in the work reflects the subtle nuances of the human psyche more vividly
Keywords: novel; author; image; hero